Cell phone usage among college students of the University of the Philippines in the Visayas. - Germo, Sharon Rose S.
The study was undertaken to know the pattern of cell phone usage among UPV college students. It genrally aims to identify the cellphone usage pattern among college students by (1) identifying the cell phone acquisition pattern of college students; (2) determining the relationship between the amount of weekly allowance of students and the means of cell phone acquisition; (3) determining the relationship between the amount of weekly allowance of students and the frequency and distribution of cell phone usage; and (4) identifying the cell phone services availed by students. The researchers used simple random sampling with replacement and employed the fishbowl sampling technique in selecting the names of the respondents. The data was gathered using the interview schedule and analyzed using simple frequency counts and percentages. the researchers also employed the chi square test for independence as a statistical tool in testing the hypothesis., The study found that most of the respondents own brand new cell phones. Those students who reported having acquired a brand new cell phone do not necessarily have big allowance. The result also shows that there is no relationship between students' weekly allowance and means of cell phone acquisition. It further shows that the frequency and duration of cell phone usage among the respondents and the amount of weekly allowance is independent. Most of the respondents end text messages that range from 1-20 in a day; make 1-3 voice call; and spend 1-10 minutes for a single voice call. The study also recognized that the respondents consider text messaging as an important feature of their cell phones. Moreover, the study revealed that most of the respondents buy cell phone accessories for their cell phones and availed of the services offered by their respective service providers. As for the recommendation, the researchers suggested to conduct a parallel study of the cell phone usage among high school students. Furthermore, it is suggested that parents' decision and preferences in purchasing cell phone for their youngster be studied.